Professional Development 21.0: Teachers, Second Languages, and CALL - Robert C. Kleinsasser (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2021)
This manuscript developed from a keynote address focusing on twenty-first Century professional development (PD) for teachers, second languages (L2), and computer assisted language learning (CALL). Participants individually and collectively were challenged to develop 21st Century PD for their language teaching, learning, and technology landscapes. PD features and design elements encouraged opportunities to acknowledge advantages and limitations as participants contemplated their 21st Century PD meaning-making potential, individually and collectively. The keynote was delivered 22 November 2019 at the 3rd UHAMKA International Conference on ELT and CALL 2019 in Jakarta, Indonesia.